(untitled) (One Health & Risk Management, 2024)
Introduction. Despite progress in Sexual and Reproductive Health (SRH) in Moldova, adolescents still face barriers accessing accurate health information and services. To address these issues, a digital resource called the YK App was developed to enhance health literacy and healthcare access for Moldovan and refugee youth. Material and methods. Three regional focus group discussions were conducted with 50 youths aged 15-24, including Ukrainian refugees. These discussions, held in multiple languages, explored participants’ SRH knowledge, information sources, barriers, and enablers Qualitative data and socio-demographic profiles were analyzed thematically and descriptively. Results. Participants rely strongly on social media for SRH information, revealing significant gaps in awareness, particularly on contraception, sexually transmitted infections, puberty and menstruation. While healthcare professionals are seen as credible sources, shame and fear of rejection often prevent direct involvement with healthcare services. Anonymity, confidentiality, and use of digital platforms were identified as key facilitators for accessing SRH information. Conclusions. The findings emphasize the potential of a digital, youth-focused SRH resource that adolescents can use independently. Key elements include clear, easy-to-understand formats such as audio and video content, and collaboration with health professionals and official health organizations to ensure credibility.